1977
DOI: 10.1113/jphysiol.1977.sp011910
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and the contractility of single muscle fibres from the barnacle Balanus nubilus

Abstract: SUMMARY1. In single striated muscle fibres from the barnacle Balanus nubilu8 tension development following axial injection of caffeine (50 mM in 150 mM-KCl, pH 7.1) was used as an index of releasable Ca. It was shown that fibres incubated in 0 Ca (Na replaced) salines for up to 400 min gave ca. 15 % of the control tension response. Inclusion of 1 mM-La in the 0 Ca (Na) saline significantly reversed this decline.2. Estimates of the total fibre calcium assayed under the same experimental conditions indicated a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
1

Year Published

1978
1978
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(32 reference statements)
3
4
1
Order By: Relevance
“…In longitudinal smooth muscle of the guinea-pig ileum, Burton & Godfraind (1974) have also observed a late lossof 45Ca after a 60 min washing in a solution containing La. Binding studies using several lanthanides and performed with various muscles have revealed similar timerelated effects as presented here (Triggle & Triggle, 1976;Ashley, Ellory & Griffiths, 1977;Grinwald & Yaari, 1978).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In longitudinal smooth muscle of the guinea-pig ileum, Burton & Godfraind (1974) have also observed a late lossof 45Ca after a 60 min washing in a solution containing La. Binding studies using several lanthanides and performed with various muscles have revealed similar timerelated effects as presented here (Triggle & Triggle, 1976;Ashley, Ellory & Griffiths, 1977;Grinwald & Yaari, 1978).…”
Section: Discussionsupporting
confidence: 59%
“…In rat myometrium, Hogdson, Kidwai & Daniel (1972) found a 14OLa accumulation of Burton & Godfraind (1974) have also observed a late lossof 45Ca after a 60 min washing in a solution containing La. Binding studies using several lanthanides and performed with various muscles have revealed similar timerelated effects as presented here (Triggle & Triggle, 1976;Ashley, Ellory & Griffiths, 1977;Grinwald & Yaari, 1978). Time curves of 45Ca efflux in La after different treatments show that at least one intracellular compartment which is loaded by agents like TEA or high K does not lose Ca into La solutions provided that the La treatment does not exceed 1 hr (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Under the assumption that the rate-limiting step of this tension development is the rate of caffeine diffusion, this result suggests that the apparent diffusion coefficient of caffeine in cardiac muscle is 15 +0-5 x 10-6cm2/s (mean+s.D., n = 8) (see Kitazawa, 1984). This value is similar to that measured directly using [14C]caffeine in barnacle muscle fibres (Ashley, Ellory & Griffiths, 1977). On the basis of the estimated concentration profile derived from the diffusion equation (see Fig.…”
supporting
confidence: 77%
“…In agreement with this, a very slow, partial recovery of pHi was often observed during a prolonged wash-off of CCCP. Absence of an effect of caffeine on CCCP-induced contracture Caffeine has been shown to release calcium from the sarcoplasmic reticulum (SR) of crustacean muscle fibres, both intact and skinned (Chiarandini, Reuben, Girardier, Katz & Grundfest, 1970;Ashley, Ellory & Griffiths, 1977). Evidence has been presented that protonophores, including CCCP, are also capable of releasing calcium from the SR (Shoshan, MacLennan & Wood, 1981).…”
Section: Effects Of Cccp On Resting Tension and Membrane Potentialmentioning
confidence: 99%